Perceived Adequacy of Resources: Reprise on a Useful Research Tool. (5th February 2021) - Nickols, Sharon Y.
Abstract : Researchers, educators, counselors, and policy‐makers use information gathered from specific populations and the public at large to identify and understand their perceptions of well‐being. Perceived Adequacy of Resources (PAR), a comprehensive exploration of individual's assessment of their resources in seven domains of living, was developed in the 1980s and has been validated as a reliable measure. In response to requests for the inventory, a summary of items in the PAR inventory is provided to facilitate further research on the topic.